1989
DOI: 10.1002/neu.480200704
|View full text |Cite
|
Sign up to set email alerts
|

Effect of putative neuromodulators on rhythmic buccal motor output in Lymnaea stagnalis

Abstract: The effects of a variety of neuromodulator substances on rhythmic motor output and activity in neurons in the feeding circuitry of Lymnaea stagnalis were examined. Each neuromodulator produced a unique combination of effects at different levels in the network: i.e., pattern-generating interneurons (N1, N2, and N3), an identified higher-order interneuron (cerebral giant cell, CGC), and buccal motoneurons. 5-Hydroxytryptamine, acetylcholine, and FMRFamide all inhibited rhythmic motor activity. However, this was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 33 publications
4
36
0
Order By: Relevance
“…Feeding-induced arousal and food intake in snails are regulated to a large extent by serotonergic 5-hydroxytryptamine (5-HT) and dopaminergic neurons (Murphy 2001, Elliott & Susswein 2002. FMRFamide and FMRFamide-containing pleural neurons both inhibit feeding and facilitate withdrawal behaviour in various gastropod species (Kyriakides & McCrohan 1989, Murphy 1990, Alania et al 2004. This is achieved by FMRFamide rapidly attenuating the rhythmic firing of buccal and cerebral ganglion neurons responsible for initiating and maintaining the repetitive motor outputs required for feeding (Alania et al 2004).…”
Section: Gastropodsmentioning
confidence: 99%
“…Feeding-induced arousal and food intake in snails are regulated to a large extent by serotonergic 5-hydroxytryptamine (5-HT) and dopaminergic neurons (Murphy 2001, Elliott & Susswein 2002. FMRFamide and FMRFamide-containing pleural neurons both inhibit feeding and facilitate withdrawal behaviour in various gastropod species (Kyriakides & McCrohan 1989, Murphy 1990, Alania et al 2004. This is achieved by FMRFamide rapidly attenuating the rhythmic firing of buccal and cerebral ganglion neurons responsible for initiating and maintaining the repetitive motor outputs required for feeding (Alania et al 2004).…”
Section: Gastropodsmentioning
confidence: 99%
“…Here we report the results of an electrophysiological study of the effects of NO on the serotonergic synapse between the cerebral giant cells (CGCs) and B4 motoneurons in the feeding system of the pond snail Lymnaea stagnalis. The CGCs are an important pair of modulatory neurons with wide ranging effects on Lymnaea feeding behavior including arousal, "gating, " frequency control, and long-term memory formation (Kemenes et al 2006;Kyriakides and McCrohan 1989;Yeoman et al 1994a,b). These effects are mediated via serotonergic synapses between the CGC and feeding interneurons and motoneurons including B4 (McCrohan and Benjamin 1980;Yeoman et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Although dopamine can activate the fictive feeding pattern in the snail CNS as can the SO and NIL interneurons (Trimble and Barker, 1984;Wieland and Gelperin, 1983;Kyriakides and McCrohan, 1989), we have not found pharmacological evidence that either the SO or the N1L releases dopamine or makes a direct contribution to dopaminergic transmission in any way. Since the buccal ganglia contain dopamine-positive cell bodies (Elekes et al, 1991), the role of dopaminergic feeding neurons (cf.…”
Section: Discussionmentioning
confidence: 58%
“…Another candidate for neurotransmitters involved in connections between the feeding intemeurons was dopamine, since dopamine applied to the tissue bath is able to evoke a strong fictive feeding rhythm in which the N1 phase is enhanced (Limax, Wieland and Trimble and Barker, 1984;Lymnaea, Kyriakides and McCrohan, 1989). Moreover in their histochemical work Elekes et al (1991) showed dopamine immunoreactive cells present in the buccal ganglia of Lymnaea close to the location of the SO and N1L inteneurons (either of which can drive fictive feeding similar to the dopamine-evoked pattern when electrically stimulated).…”
Section: Introductionmentioning
confidence: 99%